Thalictramine, A new alkaloid from Thalictrum rhyncocarpum (Dill & Rich) and its anti-bacterial activity - Mayeku, Philip Wafula; Odalo, J. O.; Hassanali, A.; Kiremire, B. T.; Hertweck, C. (My University, 2014)
Thalictrum rhyncocarpum, a creeping plant with fern-like leaves, is used in herbal medicine to treat various infections in parts of Africa. Previously, we reported In-vitro anti-bacterial activity of different parts (root, stem bark and leaves) of the plant. In this study, bioassay-guided chromatography of an active fraction of ethanol extract of the plant against Staphylococcus aures-SG 511, Pseudomonus aeruginosa-K799/61 and Mycobacterium vaccae- 10670 (using tube dilution method) was undertaken. Two bioactive constituents were isolated from an active fraction of the extract and characterized using spectrometric methods as thalictramine (1) and berberine. In addition, 6-O-β-D-glucopyranosyl-D-glucose (gentiobiose) was also isolated from the same fraction. The antibacterial activities of the active fraction, thalictramine and berberine against P. aeruginosa and M. vaccae were higher than that of ciprofloxacin.
We are grateful to the Germany Academic Exchange Program (DAAD) which provided research funds for this work. We are also thankful to the Hans Knoll Institute of Natural Product Chemistry & Infection Biology, Germany, for providing space, material and supervision for carrying out anti-bacterial assays and all spectroscopic facilities (to Mayeku Philip).
Keywords: Thalictrum rhyncocarpum; thalictramine anti-bacteria activities